Analytical insights, modulation and compositional dynamics of the feline gut microbiota: a review - Yuejun Shi; Guiqing Peng; Ashenafi Assefa Gebremariam; Muhammad Muazzam Iqbal; Hakimeh Baghaei Daemi; Muhammad Ali Khan; Rizwan Ullah; Donghan Wang (BMC, 2024)
Abstract The gastrointestinal tract of felines is inhabited by an active and intricate population of microorganisms whose alteration creates disturbances in the immune response and can affect health and disease states. Studies using various analytical methods have identified peculiar trends in various illnesses, with Firmicutes being the most prevalent phylum, followed by Bacteroidetes, Proteobacteria, and Actinobacteria. However, more Firmicutes and fewer Bacteroidetes have been observed in cats infected with Feline coronavirus. Alterations in the composition of these gut microbiota can be solved by microbiota modification through dietary fiber, probiotics, and fecal microbiota transplantation. Therefore, it is critical to understand the composition of the gut microbiota, the changes in and roles of the gut environment, and the importance of these concepts for overall health while considering the exchange of microbes between humans and domestic animals. This review provides comprehensive information on feline gut microbiota composition, modulation, and analytic methods used for characterizing the gut microbiota.